Developing information literacy and critical thinking skills through domain knowledge learning in digital classrooms: An experience of practicing flipped classroom strategy - Kong, Siu Cheung (Computers and education, 2014)
A study was conducted for creating digital classrooms to support students to develop information literacy competency and critical thinking skills through domain knowledge learning in digital classrooms. A total of 107 students from four Secondary 1 classes were invited from a secondary school in Hong Kong to participate in the study. In the 13-week trial teaching, every three students shared a Tablet PC for learning two topics in the Integrated Humanities subject. The pre- and post-tests of the two target subject topics found that the students had a statistically significant growth in domain knowledge. The three identical information literacy tests and critical thinking tests throughout the trial teaching found that the students had a statistically significant growth in information literacy competency and critical thinking skills. The semi-structured interviews found that the students and teachers positively perceived the effectiveness of the pedagogical designs of the digital classrooms on supporting the development of information literacy competency and critical thinking skills. Three implications are drawn for enhancing the pedagogical designs in digital classrooms that put emphasis on fostering students' development of information literacy competency and critical thinking skills through day-to-day domain knowledge learning in class. •The study created digital classrooms of Integrated Humanities subject in Hong Kong.•It focused on the development of information literacy and critical thinking skills.•Students successfully gained domain knowledge in the designed digital classrooms.•The students' information literacy and critical thinking skills were also fostered.•Teacher professional development related to digital classrooms is needed in future.